A randomised bite force study assessing two currently marketed denture adhesive products compared with no‐adhesive control - Roshan Varghese; Gary R. Burnett; Audrey Souverain; Avinash Patil; Ana G. Gossweiler (Wiley, 2019)
Abstract Unlike other oral care products, there are limited technologies in the denture adhesive category with the majority based on polymethyl vinyl ether/maleic anhydride (PVM/MA) polymer. Carbomer‐based denture adhesives are less well studied, and there are few clinical studies directly comparing performance of denture adhesives based on different technologies. This single‐centre, randomised, three‐treatment, three‐period, examiner‐blind, crossover study compared a carbomer‐based denture adhesive (Test adhesive) with a PVM/MA‐based adhesive (Reference adhesive) and no adhesive using incisal bite force measurements (area over baseline over 12 hr; AOB0-12) in participants with a well‐made and at least moderately well‐fitting complete maxillary denture. Eligible participants were randomised to a treatment sequence and bit on a force transducer with increasing force until their maxillary denture dislodged. This procedure was performed prior to treatment application (baseline) and at 0.5, 1, 3, 6, 9, and 12 hr following application. Forty‐four participants were included in the modified intent‐to‐treat population. AOB0-12 favoured both Test adhesive to No adhesive (difference: 2.12 lbs; 95% CI [1.25, 3.00]; p < 0.0001) and Reference adhesive to No adhesive (difference: 2.76 lbs; 95% CI [1.89, 3.63]; p < 0.0001). There was a numerical difference in AOB0-12 for Test versus Reference adhesive (−0.63 lbs; [−1.51, 0.25]); however, this was not statistically significant (p = 0.1555). Treatments were generally well tolerated. Both PVM/MA and carbomer‐based denture adhesives demonstrated statistically significantly superior denture retention compared with no adhesive over 12 hr, with no statistically significant difference between adhesives.